Reactions of Pollen of Plants from Genus Lysimachia L. on Diferrent Enviromental Conditions - Matyashuk, Raisa; Mazura, Marina; Yurchuk, Mikola (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
A cytological study of pollen of different species of the genus Lysimachia L. has been carried out. This is part of the comprehensive study of biological, anatomical, cytological, biochemical and molecular genetic features of the common species in Ukraine of this genus. The genetic collection of the genus Lysimachia has been begun to create on the territory of Feofania Park in Kyiv which is the government designated park. The general appearance and sculpture of pollen grains and the sensitivity of pollen of some species of the genus Lysimachia to different conditions of plant cultivation were studied. The pollen morphology and structure of his shell in of L. nummularia L., L. punctata L. and L. vulgaris L. studied using the scanning electron microscope. The obtained results made it possible to confirm that the shape of pollen grains, the structure of its shell are genetically determined and bear the specific features of the taxon. Growth and development of plants of Lysimachia in different conditions of the environment affect the biometric indices of pollen and its fertility. The sensitivity of pollen to exogenous conditions is elevated during the flowering of plants, compared to the phase of budding. There was a tendency towards a decrease in the diameter of pollen grains with the flower opening of the L. punctata and L. vulgaris in the cultivation of plants in conditions with increased exposure to anthropogenic factors. A high level of pollen fertility for plants of L. nummularia has been established.